“I Was Theseus in My Youth”. The perspective of senility in the artistic output of Jacek Kaczmarski - Dźwinel, Kamil (Starość i młodość w literaturze i kulturze, 2016)
The subject of the article is the issue of senility present in the artistic output of Jacek Kaczmarskifrom its beginning (Old People in the Bus from his debut programme Walls) to its end (The Old Age ofTheseus, from the volume The Tunnel, which became an inspiration for taking up this topic). Consequently,I discuss the poems in which the communication perspective can be observed with regard to thesubject experiencing the old age (The Old Age of Ovid, the above mentioned The Old Age of Theseus, OldMichelangelo and Pieta Rondanini, The Sleeping Old Poet and other poems), including the texts, in whichthe old age or an old man are the subjects of reflections (for instance The Old Age of Piotr Wysocki). Thechosen topic is supplemented with a consideration of the figure of returning and transformation the innocenceto experience — this is where the actual and indispensable comparison of the old age and youthis going to participate.